EXPERIMENTAL STUDY OF NATURAL FORMS AND THE VIBRATION FREQUENCIES OF THE COMPRESSOR BLADES OF AIRCRAFT AUXULARY POWER UNIT - M. G. Belousov; O. F. Mashoshin (Научный вестник МГТУ ГА, 2018)
The article presents the results of the blades vibration studies, where the blades are rigidly fixed to the disk of the high-pressure compressor of the auxiliary power unit (APU). The task of the study is set because of the destruction of the blades cascade, which led to the APU failure. The designated APU resource was not provided. Destruction of compressor blades occurred since the introduction of gas turbine engines, but it was not always possible to comprehensively investigate the problem and completely prevent the destruction of compressor blades. Analysis of fatigue failure statistics led to the conclusion that all the blades, regardless of their size and material are destroyed in certain areas on the back, edges and tip. The relative coordinates of the crack location are approximately the same. This indicates the availability of common patterns of the blades dynamic loading and the resulting tension in them with resonance vibrations. Moreover, the availability of operational damage on the blades does not affect these patterns. However, these patterns are not fully applicable to the blades represented in this study (wide-chord, with variable thickness from the leading to the trailing edge), but they have some similarities. The study of the forms spectrum and the blade frequency vibration is the first step in solving the problem of the blades destruction. Every detail has an infinite number of frequency characteristics that form the spectrum. Each frequency of natural oscillations corresponds to its own form of vibration. The form of the vibrations is determined by the pattern of alternating displacements or deflections and the position of the nodal lines. In nodal lines the displacements are infinitely small and considered null. The displacements of the vibrating sections on different sides of the nodal lines are in antiphase. The combination of the vibration shapes forms a variety of shapes. In this study, a sand method for determining the spectrum of vibration frequencies was used. This experiment will allow to define the sectors of defects occurrence with the subsequent development of fatigue cracks and to define real dynamic loading of the given blades design.